Pengaruh Molaritas Sodium Hidroksida terhadap Kekuatan Tekan dan Tarik Belah dari Alkali-activated Mortar Berbahan Dasar Feronikel Slag - Kuncoro, Albert; Djayaprabha, Herry Suryadi (Department of Civil Engineering, Diponegoro University, 2021)
The use of cement as the main binding agent in construction contributes approximately 7-10% in total of carbon dioxide gas emissions worldwide. In this study, the replacement of Portland cement using ground granulated ferronickel slag (GFNS) activated by the combination of sodium hydroxide (NaOH) dan sodium silicate (Na2SiO3) was utilized for producing alkali-activated mortar (AAM) as construction material. Four different mortar mixtures were prepared in this experimental work. There were three mixtures of ferronickel slag-based alkali activated mortar (FAM) with the variations of NaOH molarity of 6, 8, and 10M and cement-based mortar mixture (PCM) with water-to-cement ratio (w/c) of 0.5 was used as the control specimens. Overall, the flow and workability of the FAM specimen was lower than the PCM specimen due to the presence of silicate caused a sticky characteristic on the paste. On the other hand, the unit weight of FAM mortar was higher than the PCM specimen. Among all FAM mixtures, the most effective compressive strength and splitting tensile strength results were achieved by the FAM8 mixture, with a compressive strength at 28 days of 33.72 MPa and the splitting tensile strength at 28 days of 2.65 MPa, which had both good workability and chemical reaction of the material.